Origin of red beds and paleosols in the Palaeoproterozoic Transvaal and Olifansthoek Supergroups of South Africa: provenance versus metasomatic controls - Land, Jarred S.; Tsikos, Harilaos; Cousins, David; Luvizotto, George Luiz; Zack, Thomas (Geological journal, 2018)
The Palaeoproterozoic Transvaal and Olifantshoek Supergroups of South Africa contain some of the earliest hematite-rich sedimentary rocks (red-beds) and paleosols on record. The origin of these rocks has been variously attributed to surface processes under an oxygenated atmosphere that post-dated the ca. 2.3 Ga Great Oxidation Event (GOE). Interpretations of their geochemical signatures, however, have been inconclusive with respect to the causes of the apparent K-enrichment that these rocks record. Here, we re-visit the basal Mapedi Formation of the Olifantshoek Supergroup and the unconformably underlying Drakenstein palaeo-weathering profile that develops against the Ongeluk Formation of the upper Transvaal Supergroup, and present new petrographic and geochemical data in an attempt to constrain the burial metasomatic history of these rocks. Apart from the strong hematitic nature and K-metasomatic overprint seen in both the Mapedi Formation and Ongeluk paleosol, a curious and hitherto unexplored enrichment in high-field strength elements (HFSEs: Ti, Nb, Y, Zr, REE, etc.) by several orders of magnitude higher than average shale characterizes the lower part of the Mapedi Formation as examined here. We show that such enrichments cannot be explained by normal source-to sink weathering processes, unless an unlikely provenance of special geochemical composition (i.e. alkali igneous rocks) is to be invoked. We conclude that the HFSE enrichment, K-metasomatism and evidently transgressive Fe-oxidation effects in the Mapedi shales can only be accounted for via post-depositional fluid-rock interaction, possibly involving F-bearing diagenetic brines. This opens the distinct possibility that such fluids may have also been implicated in alteration processes, enhanced Fe mobility and development of epigenetic hematitic iron-ores as seen at the Transvaal-Olifantshoek unconformity on regional scales. Copyright © 2017 John Wiley & Sons, Ltd.
First published: 25 January 2017
Gesehen am 04.11.2019